InSnBiZnAg high-entropy alloy brazing filler metal and preparation method and application thereof

Through the use of InSnBiZnAg high-entropy alloy solder, the problem that binary Sn-based solder in the prior art cannot meet the needs of high-density interconnection and low-temperature welding is achieved, and solder joint interconnection and high reliability are achieved below 85°C. Connection meets the welding performance requirements of electronic devices.

CN119188017APending Publication Date: 2024-12-27HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)

Patent Information

Application Number
CN202411183823.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing binary Sn-based soldering is unable to meet the demand for thermally sensitive devices for high-density interconnects and low-temperature welding, especially in 3D IC packages, lacking solder with melting points below 180°C and lower than that for biomedical equipment. It is difficult to improve strength, reliability and low-temperature welding performance at 100°C. Traditional methods to improve solder joint performance at the same time.

Method used

Using InSnBiZnAg high-entropy alloy brazing, by selecting the appropriate combination of Sn, In, Bi, Zn, and Ag proportions, a multivariate alloy with low melting point, high mechanical strength and high service reliability is formed, and the slow diffusion effect of the high-entropy alloy is used to suppress welding. Overgrowth of intermetallic compounds at point interfaces enables welding below 85°C.

Benefits of technology

It realizes solder joint interconnection at extremely low temperatures (below 85℃), improves the reliability and connection strength of solder joints, meets the actual demand of electronic devices, reduces the risk of warping caused by thermal stress, and has a high cost-effectiveness. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119188017A_ABST
    Figure CN119188017A_ABST
Patent Text Reader

Abstract

The invention provides InSnBiZnAg high-entropy alloy brazing filler metal and a preparation method and application thereof, the high-entropy alloy brazing filler metal comprises the components of InSnBiZnAg, and the components comprise, by mass, 25%-35% of In, 28%-38% of Sn, 20%-30% of Bi, 2%-12% of Zn and 3%-6% of Ag. According to the technical scheme, the brazing filler metal can be used for conducting welding spot interconnection of electronic devices at the backflow temperature lower than 85 DEG C, the problem that heat-sensitive devices are damaged by high-temperature welding is solved, the warping problem caused by thermal stress is reduced, and the brazing filler metal has the advantages of being low in melting point, high in mechanical strength, high in service reliability, high in cost performance and the like; the method is especially suitable for packaging and interconnection requirements of flexible substrate electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft soldering, and in particular to an InSnBiZnAg high entropy alloy solder and a preparation method and application thereof. Background Art

[0002] With the advent of the 5G era, the upgrading of electronic products is developing towards multifunctionality and miniaturization. However, the characteristic size of chips is approaching its physical limit, which makes advanced packaging technology that integrates multiple chips vertically or horizontally an alternative method for developing electronic products in the post-Moore era. To meet this challenge, 3D integrated circuit packaging (3D IC) technology with high-density interconnection has been proposed. In 3D IC, the vertical stacking of chips is achieved through a multi-level packaging process, first using a high-melting-point SnAgCu305 solder for reflow, and then reflowing a low-melting-point solder. The use of low-melting-point solder can effectively prevent the solder joints formed during the front-end reflow process from melting again. Horizontally stacking chips will lead to an increase in package size and increase the risk of chip and PCB thermal warping caused by the mismatch of the coefficient of thermal expansion (CET) during high-temperature connection, making device failure more serious. This warping can be solved by using a low-melting-point solder during the assembly process. The use of low-temperature solder can reduce the soldering temperature and reduce the thermal stress during the product reflow process, thereby improving the reliability of the solder joints. For materials that are prone to thermal deformation and electronic components that are sensitive to temperature, using low-temperature solder can avoid damage caused by high temperature, thereby improving the yield rate of the device.

[0003] Eutectic binary Sn-based solders have been studied for decades, but there is still a lack of solders with melting points below 180°C and solders with melting points below 100°C for use in biomedical devices. Common low-temperature Sn-based solders include Sn58Bi (138°C) and Sn52In (118°C) alloys. Although Sn58Bi eutectic solder has good mechanical strength, it is highly brittle and will undergo component segregation during service, resulting in a significant reduction in reliability.

[0004] Since binary Sn-based solders cannot adapt to the rapid development of technology, the research on multi-component low-temperature solders is particularly important. The In-Sn-Bi ternary alloy solder combines the excellent properties of SnBi and SnIn, and its low melting point makes it possible to be used in flexible electronics. However, due to the complexity of the ternary system, there are currently few systematic studies on In-Sn-Bi alloys. The traditional method to improve solder joint performance is usually to add a trace amount of a third (fourth) element or nanoparticles to a binary or ternary alloy solder to form a composite solder. Although this method can partially improve the performance of the original solder, it can usually only improve certain characteristics in a targeted manner, and the overall properties of the solder will not change significantly, making it difficult to achieve simultaneous improvements in various properties such as strength, reliability, and low-temperature welding. Summary of the invention

[0005] In view of the above technical problems, the present invention discloses an InSnBiZnAg high entropy alloy solder and a preparation method and application thereof, which has a low melting point, can interconnect the solder joints of electronic devices at a reflow temperature below 85°C, and has high reliability.

[0006] To this end, the technical solution adopted by the present invention is:

[0007] An InSnBiZnAg high entropy alloy solder comprises InSnBiZnAg, wherein the mass percentages of the elements are respectively In 25-35%, Sn 28-38%, Bi 20-30%, Zn 2-12%, and Ag 3-6%.

[0008] This technical solution breaks the traditional alloy design concept and uses five elements Sn, In, Bi, Zn, and Ag to select a suitable proportion to obtain a multi-element alloy with high entropy alloy, which has the advantages of low melting point, high mechanical strength, high service reliability and high cost performance. Moreover, based on the slow diffusion effect of high entropy alloy, the solder joints prepared using this low-temperature solder have stable organization, and the performance changes little after long-term service, which can effectively inhibit the excessive growth of intermetallic compounds (IMC) at the solder joint interface and improve the reliability of the solder joint.

[0009] The solder has a low melting point and can form good wetting and spreading with the Cu substrate after melting. After heating and reflowing at 85°C for 3 minutes, it can form a good metallurgical bond with the Cu pad. The shear strength of the solder joint can reach more than 25MPa, meeting the actual needs of electronic devices in service.

[0010] As a further improvement of the present invention, the composition of the InSnBiZnAg alloy solder is In 0.2 Sn 0.8 , Bi3In5 and An5Zn8.

[0011] As a further improvement of the present invention, the mass percentages of the elements are respectively In 28.6-32%, Sn 33-35.3%, Bi 23.9-26.7%, Zn 2-12%, and Ag 4%.

[0012] As a further improvement of the present invention, the liquidus temperature of the InSnBiZnAg alloy solder is 55-120°C.

[0013] As a further improvement of the present invention, the melting temperature of the InSnBiZnAg high entropy alloy solder is 56.8°C.

[0014] The present invention also discloses a method for preparing the above-mentioned InSnBiZnAg high entropy alloy solder, comprising the following steps:

[0015] Step S1, adding pure metal raw materials In, Sn, Bi, Zn and Ag with low melting point on top and high melting point on the bottom into a crucible, that is, the adding order is Ag-Zn-Bi-Sn-In;

[0016] Step S2, placing the crucible containing the raw materials into an induction heating melting furnace, sealing the furnace chamber, evacuating the chamber, and introducing an inert gas as a protective gas until the chamber reaches a positive pressure;

[0017] Step S3, maintaining the Ar gas atmosphere, heating up the melting by electromagnetic induction heating, and cooling after the melting is completed.

[0018] As a further improvement of the present invention, in step S3, after smelting is completed, the smelted metal is taken out and water-cooled and formed. Furthermore, pure water at 15-25° C. is used to cool and form the molten liquid alloy.

[0019] As a further improvement of the present invention, the inert gas is Ar gas.

[0020] As a further improvement of the present invention, step S2 is repeated three times to complete the gas washing.

[0021] As a further improvement of the present invention, in step S2, the vacuum degree of the vacuum chamber is 1×10 -4 ~1.5×10 -4 Pa; Ar gas is introduced into the cavity until the internal pressure reaches 0.02-0.05 Pa,

[0022] As a further improvement of the present invention, in step S3, the current of induction heating is 13-15A, and the heating process temperature rise rate is 0.5-2°C / s. Furthermore, the heating process temperature rise rate is 1°C / s.

[0023] As a further improvement of the present invention, the smelting and holding temperature is 750-900° C., and the holding time is 30-60 minutes.

[0024] As a further improvement of the present invention, the cooling rate is 1-5°C / min.

[0025] As a further improvement of the present invention, in step S3, repeated smelting is performed, and the number of repetitions is ≥3 times.

[0026] The present invention also discloses the application of the InSnBiZnAg high entropy alloy solder as described above, which is used in the field of electronic packaging and can realize the interconnection of solder joints of electronic devices at an extremely low soldering temperature as low as 80°C.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] First, the technical solution of the present invention is based on the In-Sn-Bi low-temperature alloy system, and Ag and Zn elements are introduced to form a 5-element high-entropy low-temperature alloy. The mechanical properties of the low-melting-point alloy are enhanced through the mechanism of solid solution strengthening and second-phase strengthening; with the help of the slow diffusion effect of the high-entropy alloy, the excessive growth of intermetallic compounds (IMC) in the metallurgical interface layer of the solder joint during long-term service is suppressed, thereby improving the stability of the mechanical properties of the solder joint after long-term service.

[0029] Second, the high entropy alloy adopts a multi-component alloy design, in which the raw materials of Sn, Bi and Zn are low in price, which can well balance the overall cost of alloy solder manufacturing, and has a certain cost performance ratio. At an extremely low temperature of 85°C, it has good wetting and metallurgical reaction on the Cu metal substrate. After 3 minutes of welding, the strength of the connector can reach more than 25MPa, which meets the connection strength requirements of actual electronic packaging. The solder joint interface IMC is Cu6 (In, Sn, Zn) 5. The doping of multiple elements makes the diffusion movement of the substrate Cu element into the solder slow, and the excessive growth of IMC is inhibited; the interface IMC has good toughness and can absorb and release the interface thermal stress well during the thermal cycle. The solder of the technical solution of the present invention can interconnect the solder joints of electronic devices at a reflow temperature below 85°C, solves the problem of damage to heat-sensitive devices caused by high-temperature welding, reduces the warping problem caused by thermal stress, and has the advantages of low melting point, high mechanical strength, high service reliability and high cost performance. The solder joints prepared using this low-temperature solder have stable organization, small performance changes after long-term service, and have the advantage of high reliability.

[0030] Third, the technical solution of the present invention uses simple process technology, easy-to-obtain raw materials, and is highly practical. It can fill the market gap of commercial ultra-low temperature solder (melting point below 100°C) in the current electronic device packaging field and solve the packaging and connection problems of flexible electronic devices and heat-sensitive devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a flow chart for preparing the InSnBiZnAg high entropy alloy solder of the present invention.

[0032] Figure 2 The present invention is a flow chart of the preparation of the InSnBiZnAg high entropy alloy solder by reflowing on a Cu substrate to form solder joints.

[0033] Figure 3 The XRD test result diagrams of Examples 1 to 4 of the present invention are shown.

[0034] Figure 4These are SEM characterization images of the cross-sectional morphology of the solder joints of Examples 1 to 4 of the present invention, wherein the small image in the upper right corner is the IMC layer morphology of the solder joint interface highlighted after image processing; wherein, (a)-(d) are Examples 1 to 4, respectively.

[0035] Figure 5 These are SEM characterization images of the fracture morphology of the solder joints of Examples 1 to 4 of the present invention; wherein (a)-(d) are Examples 1 to 4, respectively.

[0036] Figure 6 1 and 2 are SEM images of the alloys of Example 1 and Comparative Example 1 of the present invention; wherein (a) and (b) are images of the alloy of Comparative Example 1 at different magnifications, and (c) and (d) are images of the alloy of Example 1 at different magnifications.

[0037] Figure 7 It is a DSC comparison chart of Example 3 of the present invention and Comparative Example 2 and Comparative Example 3; wherein (a), (b), and (c) are Comparative Example 2, Comparative Example 3, and Example 3, respectively. DETAILED DESCRIPTION

[0038] The preferred embodiments of the present invention are described in further detail below.

[0039] A high-reliability, low-melting-point InSnBiZnAg high-entropy alloy solder is prepared from the following raw materials according to mass percentage: In 25-35%, Sn 28-38%, Bi 20-30%, Zn 2-12%, and Ag 3-6%.

[0040] Among them, the raw material of In is a metal ingot with a purity of 99.9%; the raw material of Sn is a metal powder with a purity of 99.9%; the raw material of Bi is a metal particle with a purity of 99.9%; the raw material of Zn is a metal particle with a purity of 99.9%; and the raw material of Ag is a metal particle with a purity of 99.9%.

[0041] like Figure 1 As shown, the preparation method of the low melting point InSnBiZnAg high entropy alloy solder comprises the following steps:

[0042] 1) Using 5-10% hydrochloric acid ethanol solution, the raw metal particles are cleaned to remove surface oxides and pollutants, and ultrasound is applied during the process. The cleaning time is 3-5 minutes. After pickling, it is rinsed twice with anhydrous ethanol and dried for standby use;

[0043] 2) pure metal raw materials In, Sn, Bi, Zn and Ag are loaded into an Al2O3 crucible, and the order of loading the metal raw materials into the crucible is low melting point on top and high melting point on the bottom, that is, the order of adding is Ag-Zn-Bi-Sn-In;

[0044] 3) Place the crucible containing the raw materials into an induction heating melting furnace, seal the furnace cavity, and start the vacuum pump to extract the gas in the cavity until the vacuum degree is 1×10 -4 ~1.5×10 -4 Pa, turn off the vacuum pump, and introduce pure Ar gas as protective gas until the chamber reaches a positive pressure of 0.02-0.05 Pa. Repeat the above steps 3 times to complete the gas washing;

[0045] 4) Open the exhaust valve of the furnace chamber to maintain the Ar gas atmosphere in the chamber. Set the heating curve and perform rapid heating and melting by electromagnetic induction heating. The induction current is 13-15A; the heating rate is 1°C / s, the insulation temperature is 750-900°C; the insulation time is 30-60 minutes. After melting, the metal is cooled to room temperature with the furnace, and the cooling rate is 1-5°C / min. Repeat the melting for ≥3 times;

[0046] 5) After completing the above smelting step, the crucible is taken out from the smelting furnace, and the liquid alloy is water-cooled and rapidly formed to obtain the InSnBiZnAg high entropy alloy solder;

[0047] 6) The alloy formed by cooling is pressed into a mold to produce a brazing foil.

[0048] The prepared InSnBiZnAg high entropy alloy solder has high reliability and low melting point, can be used in the field of electronic packaging, and can achieve low-temperature welding.

[0049] The following describes the invention in conjunction with specific embodiments.

[0050] Example 1

[0051] 1) Weigh and proportion the raw metals, where In is 32g, Sn is 35.3g, Bi is 26.7g, Zn is 2g, and Ag is 4g, totaling 100g. Use 5-10% hydrochloric acid ethanol solution to clean and remove surface oxides and contaminants from the raw metal particles, apply ultrasound during the process, and the cleaning time is 3-5 minutes. After pickling, rinse with anhydrous ethanol twice and dry for use;

[0052] 2) pure metal raw materials In, Sn, Bi, Zn and Ag are loaded into an Al2O3 crucible, and the order of loading the metal raw materials into the crucible is low melting point on top and high melting point on the bottom, that is, the order of adding is Ag-Zn-Bi-Sn-In;

[0053] 3) Place the crucible containing the raw materials into an induction heating melting furnace, seal the furnace cavity, and start the vacuum pump to extract the gas in the cavity until the vacuum degree is 1.3×10 -4 Pa, turn off the vacuum pump, and introduce pure Ar gas as protective gas until the chamber reaches a positive pressure of 0.04 Pa. Repeat the above steps 3 times to complete the gas washing;

[0054] 4) Open the exhaust valve of the furnace chamber to maintain the Ar gas atmosphere in the chamber. Set the heating curve and perform rapid heating and melting by electromagnetic induction heating. The induction current is 14.2A; the heating rate is 1℃ / s, the insulation temperature is 850℃; the insulation time is 60 minutes. After melting, the metal is cooled to room temperature with the furnace, and the cooling rate is 2℃ / min. Repeat the melting for ≥3 times;

[0055] 5) After completing the above smelting step, the crucible is taken out from the smelting furnace, and the liquid alloy is water-cooled and rapidly formed to obtain InSnBiZnAg high entropy alloy solder;

[0056] 6) The alloy formed by cooling is pressed into a mold to produce a brazing foil.

[0057] Example 2

[0058] The preparation method is the same as that of Example 1, except that: In is 31.4 g; Sn is 34.5 g; Bi is 26.1 g; Zn is 4 g; Ag is 4 g; and the total is 100 g.

[0059] Example 3

[0060] The preparation method is the same as that of Example 1, except that: In is 30 g; Sn is 33 g; Bi is 25 g; Zn is 8 g; Ag is 4 g; a total of 100 g.

[0061] Example 4

[0062] The preparation method is the same as that of Example 1, except that: In is 28.6 g; Sn is 34.5 g; Bi is 23.9 g; Zn is 12 g; Ag is 4 g; a total of 100 g.

[0063] Test Example 1

[0064] The phase composition of the alloys obtained in Examples 1 to 4 was characterized and tested. The results are as follows: Figure 3 As shown, the results show that the alloy solders prepared in Examples 1 to 4 are mainly composed of In 0.2 Sn 0.8 , Bi3In5 and An5Zn8.

[0065] Test Example 2

[0066] The melting properties of the low melting point InSnBiZnAg high entropy alloy solders of Examples 1 to 4 were tested, and the solidus line in the DSC curve was used as the melting point, and the results were recorded in Table 1. The results show that the melting points of the alloy solders of Examples 1 to 4 are all lower than 60°C. According to experience, the reflow temperature of the solder joints in electronic packaging is usually +15 to 20°C of the solder melting point. Therefore, the alloy solders in Examples 1 to 4 can achieve solder joint interconnection at a soldering temperature of 80°C.

[0067] Table 1 Performance test results of Examples 1 to 4

[0068]

[0069] Test Example 3

[0070] The low melting point InSnBiZnAg high entropy alloy solders of Examples 1 to 4 were tested for wettability on a Cu substrate and shear performance of the soldered joints. The results are recorded in Table 1. The preparation process of the low melting point InSnBiZnAg high entropy alloy solder for reflowing to form solder joints on a Cu substrate is as follows: Figure 2 As shown, the size of the Cu lower substrate is 10mm×10mm×1mm; the size of the Cu upper substrate is 5mm×5mm×1mm; the size of the InSnBiZnAg high entropy alloy brazing foil is 5mm×5mm×0.1mm. During welding, an appropriate amount of low-temperature flux is applied to both sides of the brazing foil, and after heating in a reflow oven at 80°C for 3 minutes, it is naturally cooled to form a solder joint, and the shear performance of the solder joint is measured using a micromechanical structure tester. Similarly, the brazing foils of Examples 1 to 4 with a size of 5mm×5mm×0.1mm are heated at 80°C for 3 minutes on a Cu substrate, and their wetting spread area is measured using a volume microscope.

[0071] According to the performance test results of Examples 1 to 4 in Table 1, the low melting point InSnBiZnAg high entropy alloy solder prepared by the present invention can form good spreading and wetting on the Cu substrate at a relatively low temperature (80°C). The increase in the content of Zn in the alloy solder composition reduces the wettability of the solder due to its active and easily oxidizable nature, so the content of the Zn component in the InSnBiZnAg high entropy alloy solder should be controlled within the range described in the present invention.

[0072] The cross-sectional morphology of the solder joints of Examples 1 to 4 is as follows: Figure 4 As shown, it can be seen that the IMC layer is formed by the metallurgical reaction between the solder and the Cu substrate, which ensures good mechanical properties of the solder joint.

[0073] Test Example 4

[0074] The morphology of the solder joint fractures of Examples 1 to 4 after the shear test in Test Example 3 was observed and characterized. Figure 5 As shown. According to the observation in the fracture, the plastic deformation caused by the external shear force leaves tearing to generate dimples and micropores, indicating that the solder joint prepared by the InSnBiZnAg high entropy alloy solder of the present invention has good toughness, and its fracture mode is ductile fracture.

[0075] Comparative Example 1

[0076] InSnBiZnGa, using the existing technology, its components and atomic molar percentages are: Sn is 20.0%, Bi is 20.0%, In is 20.0%, Zn is 20.0%, Ga is 20.0%, and the preparation steps are as follows: Prepare 100g of raw materials Sn, Bi, In, Zn, and Ga with a purity greater than 99.99% according to equal atomic molar percentages. Put the prepared raw materials into the corundum crucible in order from high to low melting points, with the element with the lowest melting point on the top. Put the corundum crucible filled with alloy materials into the spiral induction coil in the high vacuum induction melting casting furnace, and evacuate with a mechanical pump for 20 minutes, then turn off the vacuum pump and fill it with high-purity argon gas with a purity of 99.99% to normal atmospheric pressure to complete a purge process. The purge process is repeated three times, and after the last purge, the high-purity argon gas is filled to a positive pressure of 0.04MPa. After adjusting the current to 180A for preheating for 2 minutes, increase the current to 200A for heating for 4 minutes. When the alloy is completely in a golden liquid state, turn off the induction current heating and pour it into a copper mold for cooling. The alloy obtained in Comparative Example 1 is welded using the method in Test Example 3. The shear strength of the obtained joint is about 8Mpa, which is much lower than the shear strength of each embodiment in Table 1. This is mainly because the strength and creep resistance of the Ga-containing high entropy alloy are weak. Since it is difficult for the Ga element to form a eutectic with other metal elements, the high entropy alloy structure is severely segregated and the alloy performance is poor.

[0077] The InSnBiZnAg alloy of Example 1 can form eutectic structures such as Zn-Ag, Sn-Ag, In-Ag, etc.

[0078] The microstructures of the alloy solders obtained in Example 1 and Comparative Example 1 were observed. Figure 6 As shown, it can be seen that compared with Comparative Example 1, the InSnBiZnAg alloy obtained in Example 1 has a uniform microstructure and morphology, and has better performance while ensuring the low melting point characteristics of the alloy.

[0079] Comparative Example 2

[0080] The preparation method is the same as that of Example 1, except that: In is 24g; Sn is 42g; Bi is 18g; Zn is 14g; Ag is 2g; a total of 100g. The contents of In, Sn, Bi, Zn and Ag components in this comparative example are not within the range described in claim 1. The alloy solder prepared in this comparative example was subjected to a DSC curve test, and the results showed that the alloy had a double-peak melting point, which appeared at 59.8°C and 138.3°C respectively. The alloy obtained in Comparative Example 1 was welded using the method in Test Example 3. Since the alloy solder was only partially melted at a low temperature of 85°C, it was unable to form a good metallurgical bond with the substrate under the low reflux temperature of 85°C, and the shear strength of the joint was less than 10Mpa.

[0081] Comparative Example 3

[0082] The preparation method is the same as that of Example 1, except that: In is 20g; Sn is 53g; Bi is 15g; Zn is 8g; Ag is 4g; a total of 100g. The contents of In, Sn and Bi components in this comparative example are not within the range described in claim 1. The alloy solder prepared in this comparative example was subjected to a DSC curve test, and its melting range was relatively wide, with a melting starting point of 70.4°C and a melting peak of 162.4°C. The alloy obtained in comparative example 1 was welded using the method in test example 3. Since the mechanical strength of the component alloy itself is relatively poor, although the joint can form a metallurgical bond, the shear strength is lower than 15Mpa. Compared with experimental examples 1 to 4, the mechanical properties of the joint are relatively poor.

[0083] Comparative Example 2, Comparative Example 3 and Experimental Example 3 were subjected to DSC test. The test curve results are shown in Figure 7 As shown in the figure, it can be seen from the comparison that Experimental Example 3 has a greater low-temperature reflow soldering advantage in terms of melting performance compared with Comparative Examples 2 and 3.

[0084] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. InSnBiZnAg high entropy alloy solder, characterized by: Its composition is InSnBiZnAg, wherein the mass percentages of the elements are respectively In 25-35%, Sn 28-38%, Bi 20-30%, Zn 2-12%, and Ag 3-6%.

2. The InSnBiZnAg high entropy alloy solder according to claim 1, characterized in that: The liquidus temperature of the InSnBiZnAg alloy solder is 55-120°C.

3. The InSnBiZnAg high entropy alloy solder according to claim 2, characterized in that: The melting temperature of the InSnBiZnAg high entropy alloy solder is 56.8°C.

4. The method for preparing the InSnBiZnAg high entropy alloy solder according to claim 1, characterized in that: The steps include: Step S1, pure metal raw materials In, Sn, Bi, Zn and Ag are placed into a crucible in the order of low melting point on top and high melting point on the bottom; Step S2, placing the crucible containing the raw materials into an induction heating melting furnace, sealing the furnace chamber, evacuating the chamber, and introducing an inert gas as a protective gas until the chamber reaches a positive pressure; Step S3, maintaining an Ar gas atmosphere, heating the material to 750-900° C. by electromagnetic induction heating for smelting, and cooling the material after smelting is completed.

5. The method for preparing the InSnBiZnAg high entropy alloy solder according to claim 4, characterized in that: In step S3, after smelting is completed, the smelted metal is taken out and water-cooled to form.

6. The method for preparing the InSnBiZnAg high entropy alloy solder according to claim 5, characterized in that: The molten alloy is cooled and molded using pure water at 15 to 25°C.

7. The method for preparing the InSnBiZnAg high entropy alloy solder according to claim 4, characterized in that: Step S2 is repeated three times to complete the gas washing.

8. The method for preparing the InSnBiZnAg high entropy alloy solder according to claim 4, characterized in that: In step S2, the vacuum degree of the vacuum chamber is 1×10 -4 ~1.5×10 -4 Pa; Ar gas is introduced into the cavity until the internal pressure reaches 0.02-0.05 Pa; In step S3, the current of induction heating is 13-15A, the heating rate of the heating process is 0.5-2°C / s; the melting and holding time is 30-60 minutes, and the cooling rate is 1-5°C / min.

9. The method for preparing the InSnBiZnAg high entropy alloy solder according to claim 4, characterized in that: In step S3, repeated smelting is performed, and the number of repetitions is ≥ 3 times.

10. Use of the InSnBiZnAg high entropy alloy solder according to any one of claims 1 to 3, characterized in that: Used in the field of electronic packaging.

Citation Information

Patent Citations

  • Sn-Bi-In-Zn-Ga low-melting-point high-entropy alloy lead-free solder and preparation method and application thereof

    CN112958941A

  • Sn-Bi-In-Ag lead-free solder suitable for low-temperature welding and preparation method of Sn-Bi-In-Ag lead-free solder

    CN117900692A

  • Sn-Bi-In-Ag-Zn high-reliability high-entropy alloy low-temperature solder for advanced packaging and preparation method of Sn-Bi-In-Ag-Zn high-reliability high-entropy alloy low-temperature solder

    CN119820172A

Cited By

  • Ag particle modified equal-atomic-ratio multi-element composite electronic paste and preparation method of high-shear-strength low-void-ratio packaging welding spots of Ag particle modified equal-atomic-ratio multi-element composite electronic paste

    CN120862151A